2006
DOI: 10.1016/j.trstmh.2005.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Malaria treatment in remote areas of Mali: use of modern and traditional medicines, patient outcome

Abstract: Summary Use of official health services often remains low despite great efforts to improve quality of care. Are informal treatments responsible for keeping a number of patients away from standard care, and if so, why? Through a questionnaire survey with proportional cluster samples, we studied the case histories of 952 children in Bandiagara and Sikasso areas of Mali. Most children with reported uncomplicated malaria were first treated at home (87%) with modern medicines alone (40%), a mixture of modern and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 7 publications
(7 reference statements)
1
51
0
Order By: Relevance
“…2 Local communities in Mali use herbal preparations as the first treatment for more than 80% of malaria episodes. 3 Argemone mexicana (AM) decoction was selected as the most promising from 160 traditional recipes. [3][4][5] plant is all the more interesting because it is widespread throughout the tropics (including Latin America and Asia).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Local communities in Mali use herbal preparations as the first treatment for more than 80% of malaria episodes. 3 Argemone mexicana (AM) decoction was selected as the most promising from 160 traditional recipes. [3][4][5] plant is all the more interesting because it is widespread throughout the tropics (including Latin America and Asia).…”
Section: Introductionmentioning
confidence: 99%
“…3 Argemone mexicana (AM) decoction was selected as the most promising from 160 traditional recipes. [3][4][5] plant is all the more interesting because it is widespread throughout the tropics (including Latin America and Asia). After completion of toxicological studies, a dose-escalating clinical study showed a dose response, no serious adverse events and a sharp decline in parasitaemia (from a geometric mean of 14 859 at day 0 to a geometric mean of 174 parasites per mcl at day 4) although generally without total parasite clearance.…”
Section: Introductionmentioning
confidence: 99%
“…It is also used as an antimalarial in several African countries, including Benin, Mali and Sudan. Its in vitro efficacy against P. falciparum has been confirmed by several studies (Adjobimey et al, 2004;Diallo et al, 2006;Simonsen et al, 2001). No previous clinical studies have been conducted to determine its safety and efficacy in human patients.…”
Section: Introductionmentioning
confidence: 91%
“…Currently, a mixture of three herbs called 'Malarial' is marketed as an antimalarial (Diallo et al, 2004) but it has never been tested in children under the age of 5 years. This study was undertaken to provide data that could support the development of a new MTA as well as official recommendations on the use of local resources in situations where standard modern drugs are lacking despite all possible efforts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation